Dynamic pricing as a challenge for consumer price statistics - Christian Blaudow; Florian Burg (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2018)
The use of automated algorithms allows online shops to change product prices at short notice, depending on various parameters; this type of price-setting is known as dynamic pricing. At present, roughly 10 000 online prices are collected each month by the German Federal Statistical Office (FSO) for the German consumer price index (CPI) and the harmonised index of consumer prices (HICP), but in many cases only one price is observed each month for each product, usually at a given point in time. Dynamic pricing poses a potential challenge to consumer price statistics: to capture the correct monthly average price and to process volatile prices. To understand this challenge, a study on dynamic pricing was conducted in 2017. It was limited to products and online shops that were included in the CPI/HICP sample and used web scraping to collect prices.
Keywords: 330; consumer price index; harmonised index of consumer prices; dynamic pricing; online price collection; web scraping